A Study on Factors Influencing Women Customers towards Choice of Insurance Company - Poornima, S (International Journal of Engineering and Management Research, 2025)
The insurance sector in India is a fast-growing industry that plays a essential role in the country’s economy. The objective of the research paper is to study the demographic profile of the Women customer and to identify various factors influencing women customer’s choice for insurance company. For this study, a random sampling technique has been adopted. The present study has been conducted in the State of Karnataka. The sample size 386 individuals who had an experience of offline and online insurance systems were taken. A statistical tool used is Percentage analysis and Mean. To achieve the above objectives the researcher identified 25 factors for choosing the insurance company. From the above study, researchers conclude that the insurance company management should analyze all these factors and give due weightage to these factors and make appropriate marketing strategies to retain and attract the potential customers in order to increase their market share and profits.